Viewership analysis of News Channels with special reference to Asianet News - S. Kurup, Vishnu; Nair, Vilas (International Multidisciplinary Research Journal, 2017)
The research conducted on the topic â€˜Viewership analysis of News channels with special reference to Asianet news is basically a comparative analysis of 4 leading News channels in the region.. The researchÂ comprises of the response obtained out of a sample of news channel viewers and a study on the various aspects of the news channels that are preferred by viewers with an investigation on the reasons for the same. Here, primary data was obtained by methods of Direct interviews, Telephonic Interviews and also by mail using a well-designed and structured questionnaire. Dichotomous scale, Semantic differential scale and Likert scale are the commonly used scales of measurement for the topic under study. The study focuses on finding out the reasons behind the comparatively lower rating of Asianet news in the city of Cochin. Simultaneously, it also tends to investigate on various attributes such as the news viewership pattern in the region, the core competencies of each news channel, the approximate time a viewer spends watching news a day, the opinion on the content of news programs, the preference of the viewers towards the presentation styles, news readers, graphic content and the like and also the category of news most preferred by the viewers. Random and convenience sampling techniques were used for the data collection procedure. The result ultimately suggests that Asianet News isÂ preferred byÂ majority of the viewers followed by Manorama News which leads in certain attributes like credibility of News content, accuracy of reports, Unbiased reporting of news, deep analysis and detailing, presentation styles and latest news updates . Certain key factors such the attitude and presentation style of the News Reader, unbiased analysis of the news content and strong preference towards political satires are also found to be influential in driving higher rating and viewership for the channels.